Perancangan Sistem Informasi Pendaftaran Pasien Rawat Jalan Pada Rumah Sakit Ibu dan Anak Gizar Berbasis Mobile - Asworowati, Ratih Dwi; Mustomi, Dede; Adawia, Popon Rabia; Suhendra, Asep Dony; Natong, Asriani; Cahya Ningrum, Maharani (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
In accordance with the Regulation of the Minister of Health of the Republic of Indonesia Number 82 of 2013 concerning Hospital Management Information Systems, that every Hospital is required to organize SIMRS. SIMRS regulation aims to improve efficiency, effectiveness, professionalism, performance, and hospital access and services. RSIA Gizar will start implementing SIMRS in 2021, but the current system is still not optimal because patient registration is still done directly at the hospital, cannot be done online, which makes patient registration services slow. The method of data collection used in the preparation of this Final Project is the method of observation, interviews, literature study and the software development model using the waterfall method. So that the Design of an Outpatient Patient Registration Information System uses the waterfall method. At RSIA Gizar, it was made aiming to make it easier for patients to register online through a mobile-based application and also to make it easier for admin staff to register patients, manage medical record data and in making patient registration reports so that more effective and efficient..